Activists Against Autocrats: TSMO Networks and Democratic Diffusion - Pinckney, Jonathan; Chin, John Joseph (Frontiers in Political Science, 2021)
Do transnational social movement organizations (TSMOs) promote the international diffusion of democracy? If so, how? Scholars of democratization have studied a plethora of international factors in the spread of democracy, including geographic or regional proximity, colonial history, trade and alliance networks, and joint inter-governmental organization (IGO) memberships. Few have studied the role of TSMO networks in democratic diffusion. We theorize that TSMOs empower and connect civil societies and thus promote democracy from the “bottom up.” Leveraging a new TSMO Dataset and data on the dimensions of democracy from the Varieties of Democracy project over the 1953–2013 period, we find that TSMOs promote democratic diffusion. TSMOs are strongest at diffusing participatory democracy. TSMOs also contribute to the diffusion of electoral democracy but do so by promoting the diffusion of freedom of association and freedom of expression rather than elections.